Pemikiran Ekonomi Al-Ghazali Terhadap Ekonomi Modern - Anugrah Permana Tanjung; B Miftahul Zannah Siregar; Delia Torsa Purba; Dimas Surya (Pusat Riset dan Inovasi Nasional, 2024)
Al-Ghazali's views regarding economics and business are not only limited to the philosophical realm, but are a synthesis between realities that occur in a society that has philosophical principles supported by reasonable reasons. Al-Ghazali based his theory on the school of Sufism in relation to business economics, which is reflected in his work, the book Ihya 'Ulum al-Din. Al-Ghazali considered many commercial and economic aspects of society, including the hierarchy1 of utility4 and its characteristics6 in determining social tasks related to welfare (mashlahah). He emphasized that individual behavioral intentions that are in harmony with Divine rules in every economic activity have the value of worship. Apart from that, Al-Ghazali views safety as the ultimate goal. His theoretical ideas about market exchange and growth, activities and hierarchies of production, barter systems and the use of money, the role of the state in creating a just, peaceful, and stable economy, and public financing are all relevant today.